Play analysis concerning a ball throwing-in team at lineout in rugby games - Hayasaka, K. (7th World Congress on Science and Football (WCSF), 2011, 2011)
This study conducted play analysis by carefully selecting and segmentalizing data of Japan Rugby Top League`s lineout plays in the season of 2007 which was posted in Rugby Science Study issued by Japan Rugby Football Union. The purpose is to classify play structure into three situations and clarify tendency and structure in view of ball-winning rate and effective winning rate in order to contribute to unit skill improvement of lineout plays. Methods Game analysis was conducted targeting Top League`s 20 close games in the season of 2007. The plays were divided into three situations (ball-dead, throw-in and contest) in order to analyze total ball winning rate and effective winning rate, and the result was sought by classifying into totally 10 analysis items. Result verification of significant difference was conducted by using Fischer`s exact test, and multiple comparison was conducted for significant difference. Results & Discussion The result showed that winning rate is reduced more at all-men lineout than short lineout and "backward" than "middle" for "the number of players" and "throw-in" in throw-in situation These results indicated effectiveness of forward throw-in which generates catching space and does not cause reduction of throw-in accuracy when structuring pickoff play. Furthermore, in contest situation, against contest to the upper part of an "air" jumper, plays which do not generate defense obtained total ball winning rate. Additionally, it was clarified that defense for a jumper by "landing" is a cause of reducing effective winning rate. The necessity of proficiency of pickoff plays which do not generate contest for a jumper and plays which can maintain effective winning after ball winning was inferred from these results. Conclusion Ball-winning rate is reduced when confronting defense at short lineout, backward throw-in and contest in the top level of Japanese rugby.